Subject to Review? Consideration, Liquidated Damages and the Penalty Jurisdiction - MIK, Eliza (Institutional Knowledge at Singapore Management University, 2014)
The paper examines the relationship between what seem to be basic principles in contract law: "consideration need not be adequate" and "the rule against penalties applies only to sums payable on breach." The 'reluctant inspiration' lies in the recent Australian case of Andrews v. Australia and New Zealand Banking Group Ltd, which establishes that the absence of breach or an obligation to avoid the occurrence of an event upon which a sum becomes payable, does not render such sum incapable of being characterized as a penalty. This decision constitutes an unexpected divergence from the position in most other common law jurisdictions. What are its practical implications? Should we even engage in historical arguments given that the penalty jurisdiction evolved at the time where the law did not recognize enforceable promises to perform? The paper commences with broad observations regarding the enforceability of liquidated damages clauses, the increasingly commercial approach to evaluating whether a pre-estimate of loss is "genuine" and the necessity to treat sums payable on breach as part of the commercial bargain. The more liberal the attitude with regards to the amount (i.e. the higher the sum that can be stipulated), the more limited the effect of the rule against penalties. A liberal approach does not affect the contract breaker’s ability to invoke the rule but his ability to succeed. In combination with the description of the performance, the price and the limitation of liability (if any), sums payable on breach often point towards a transaction-specific risk allocation. In many instances such sums come dangerously close to primary obligations. And courts do not, as a matter of principle, review primary obligations. Once this is acknowledged, it becomes even more difficult to justify any attempts to expand the scope of the penalty jurisdiction beyond payments triggered by breach. After confronting some of the historical arguments made by the court in Andrews, the paper analyzes the recurring attempts to extend judicial review of contractual payments by creating "hybrid stipulations" – sums that are neither payable on breach nor in return for contractual performance. A difficult theoretical exercise awaits: should we create artificial divisions between contractual payments to establish whether they can be reviewed? Or should we finally acknowledge that all sums payable under a contract are part of the commercial bargain? On one hand, doctrinal integrity may point towards the need to vigorously defend the present form of the rule against penalties, including its (seemingly) strict limitation to sums payable on breach. On the other, some arguments made in Andrews and in other recent cases highlight the theoretical inconsistencies of its current formulation. After all, the "breach/no breach" dichotomy can also be regarded as a device for avoiding judicial scrutiny. At present, on the basis of Andrews alone it appears incorrect to use an institution that prohibits deterrence from breach to review the commercial substance of contracts. The rule against penalties reflects the general equitable principle not to enforce oppressive or unconscionable transactions. It does not reform commercially imprudent transactions. Given its exceptional nature, the penalty jurisdiction should be exercised sparingly – even with regards to sums payable on breach. Once sums payable on breach are regarded as part of commercial bargain, it is more difficult to subject them to review. If, however, payment is unrelated to the breach of a contractual promise, it comes dangerously close to being a contractual promise. Any review seems unacceptable.